Crohn's & Colitis Australia inflammatory bowel disease audit: measuring the quality of care in Australia. Issue 7 (11th July 2019) - Massuger, Wayne; Moore, Gregory T. C.; Andrews, Jane M.; Kilkenny, Monique F.; Reyneke, Megan; Knowles, Simon; Purcell, Liz; Alex, George; Buckton, Stephanie; Page, Amy T.; Stocks, Nigel; Cameron, Don; et al.
Abstract: Background: Australia has among the highest prevalence of Crohn disease and ulcerative colitis in the world. Management of the chronic gastrointestinal disorders results in significant societal costs and the standard of care is inconsistent across Australia. Aim: To audit the quality of care received by patients admitted for inflammatory bowel disease (IBD) across Australia against national IBD standards. Methods: A retrospective cross‐sectional survey and clinical audit was undertaken assessing organisational resources, clinical processes and outcome measures. This study was conducted in Australian hospitals that care for inpatients with Crohn disease or ulcerative colitis. The main outcome measures were adherence to national IBD standards and comparison of quality of care between hospitals with and without multidisciplinary IBD services. Results: A total of 71 hospitals completed the organisational survey. Only one hospital had a complete multidisciplinary IBD service and 17 had a partial IBD service (IBD nurse, helpline and clinical lead). A total of 1440 inpatient records was reviewed from 52 hospitals (mean age 37 years; 51% female, 53% Crohn disease), approximately 26% of IBD inpatient episodes over a 12‐month period in Australia. These patients were chronically unwell with high rates of anaemia (30%) and frequent readmissions (40% within 2 years). In general, care was inconsistent, and documentation was poor. Hospitals with a partial IBD service performed better in many processes and outcome measures: for example, 22% reduction in admissions through emergency departments and greater adherence to standards for safety monitoring of biological (89% vs 59%) and immunosuppressive drugs (79% vs 55%) in those hospitals than those without. Conclusion: Patients admitted to hospital suffering from IBD are young, chronically unwell and are subject to substantial variations in clinical documentation and quality of care. Only one hospital met accepted standards for multidisciplinary care; hospitals with even a minimal IBD service provided improved care.